"He Who Has the Spirits Must Work a Lot": A Psycho‐Anthropological Account of Spirit Possession in the Dominican Republic. (29th October 2018) - Cardeña, Etzel; Schaffler, Yvonne
Abstract: In this paper we present a multidisciplinary, developmental analysis of a Dominican Republic Vodou servidor ("Marcos"), from childhood to early adulthood, integrating ethnographic observation, field documentation, and anthropological analysis, with relevant constructs from developmental, personality, and clinical psychology. Marcos transitioned from a child with many problems to a young adult who has learnt how to control and adapt dissociative manifestations into a professional role as a Vodou priest. Most empirical studies on spirit possession (SP) have rarely taken a longitudinal, multidisciplinary approach, which may better account for such a complex phenomenon. Adopting such an approach helps make sense of both the continuity and changes in Marcos, as well as of his community's shifting attitudes towards him. We describe how specific psychological and cultural conditions help explain the change from originally dysfunctional expressions of SP to personally and socially beneficial ones. [anomalous experience, dissociation, gender, spirit possession, Vodou]